How Far That Little Candle Throws His Beams! An Interview With Mats Isaksson. (October 2018) - Merendino, Alessandro; Goergen, Marc
This article adopts a policy-maker perspective on corporate governance, while exploring the role of academia in influencing corporate governance principles, the reasons for the boilerplate approach to governance rules typically adopted by most companies, and the reasons for a possible disconnect between research and corporate governance policies. The article ends with some key lessons about corporate governance and the future research agenda.